2015
DOI: 10.1039/c5ob00336a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nisin AB dicarba analogs using ring-closing metathesis: influence of sp3versus sp2hybridization of the α-carbon atom of residues dehydrobutyrine-2 and dehydroalanine-5 on the lipid II binding affinity

Abstract: Herein the synthesis of two nisin AB dicarba analogs is described, focusing on amino acid modifications at positions 2 and 5. The nisin mimics were synthesized by a combination of solid phase synthesis of the linear peptides, followed by macrocyclization via ring-closing metathesis and fragment assembly by means of solution phase chemistry. The two N-terminal nisin AB-fragment mimics contain either the native dehydrobutyrine (Dhb)/dehydroalanine (Dha) amino acid residues or alanine at position 2 and 5, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…In order to accelerate computations and decrease the dimensions of the system we decided to focus on a truncated nisin analogue -its www.nature.com/scientificreports www.nature.com/scientificreports/ recognition module, containing just rings A and B. This N-terminal fragment, further referred to as nisin 1-11 , seems to be an optimal choice for MD simulations, as it is the minimal nisin analogue, retaining antimicrobial activity 28,39 (most probably by depleting lipid II pool in the bacterial membrane). To confirm the conformational space similarity of the recognition module on its own and as a part of the whole nisin, we performed two series of MD simulations (see Methods).…”
Section: Conformational Dynamics Of Nisin and Its Recognition Module mentioning
confidence: 99%
“…In order to accelerate computations and decrease the dimensions of the system we decided to focus on a truncated nisin analogue -its www.nature.com/scientificreports www.nature.com/scientificreports/ recognition module, containing just rings A and B. This N-terminal fragment, further referred to as nisin 1-11 , seems to be an optimal choice for MD simulations, as it is the minimal nisin analogue, retaining antimicrobial activity 28,39 (most probably by depleting lipid II pool in the bacterial membrane). To confirm the conformational space similarity of the recognition module on its own and as a part of the whole nisin, we performed two series of MD simulations (see Methods).…”
Section: Conformational Dynamics Of Nisin and Its Recognition Module mentioning
confidence: 99%
“…Application of CuCl2 and EDC was employed at a late stage in the formation AB-dicarba analogs of nisin and allowed simultaneous elimination of the two hydroxy-groups in (69), to stereoselectively construct the Zconfigured dehydrobutyrine derivative (70) (see Scheme 13A). 88 The use of DBU in generation of (70) allowed more expedient elimination from isourea intermediates generated from (69), but is generally not required. In the synthesis of macrocyclic precursors of the vioprolides, which are depsipeptidic macrocyclic natural products containing (E)-dehydrobutyrine and thiazoline moieties, the dehydration from threonine derivatives (71) and (74) was performed using CuCl2 and EDC to engender (E)-dehydrobutyrine products (73) and (76) (Scheme 13B).…”
Section: Cucl/carbodiimide Conditionsmentioning
confidence: 99%
“…Slootweg et al synthesized dicarba bridged analogues of nisin(1-12)b yR CM, finding that replacement of (Me)Lan with longer dicarba bridges was reasonably well tolerated. [34] As parto ft his work the authors also investigated the effect of replacing both Dha and Dhb with Ala, and found that the presence of the dehydro residues increased the affinity of the dicarbab ridged peptides for lipid II. Introduction of at hirdc yclic constraint in dicarbab ridged analogueso fn isin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), by creating al actam bridge between the N-terminus and the Br ing, has also been investigated by Harmsen et al [35] The resulting reduction in flexibility increased the affinity of the peptide for lipid II over the bicyclic dicarba analogue, but was still five-fold less active than WT nisin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Slootweg et al. synthesized dicarba bridged analogues of nisin(1–12) by RCM, finding that replacement of (Me)Lan with longer dicarba bridges was reasonably well tolerated . As part of this work the authors also investigated the effect of replacing both Dha and Dhb with Ala, and found that the presence of the dehydro residues increased the affinity of the dicarba bridged peptides for lipid II.…”
Section: Introductionmentioning
confidence: 99%